2018
DOI: 10.3390/s18124375
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Gaussian Plume Model to Localization of an Indoor Gas Source with a Mobile Robot

Abstract: The source localization of gas leaks is important to avoid any potential danger to the surroundings or the probable waste of resources. Currently there are several localization methods using robotic systems that try to find the origin of a gas plume. Many of these methods require wind velocity information involving the use of commercial anemometric systems which are extremely expensive compared to metal oxide gas sensors. This article proposes the validation of the Gaussian plume model inside an empty room and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The main reason for this phenomenon was the vertical distance between the gas source (located at ground level) and the gas sensor (55 cm above the ground), combined with the air currents induced by the HVAC system, causing the plume to be pushed away from the source. This was already observed by Sánchez-Sosa et al [30] and is later confirmed by results obtained with the HVAC system turned off.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The main reason for this phenomenon was the vertical distance between the gas source (located at ground level) and the gas sensor (55 cm above the ground), combined with the air currents induced by the HVAC system, causing the plume to be pushed away from the source. This was already observed by Sánchez-Sosa et al [30] and is later confirmed by results obtained with the HVAC system turned off.…”
Section: Resultssupporting
confidence: 85%
“…The novelty of this contribution lies in the number of MOX sensors used, on the low concentrations of the target gas, on the presence of chemical interferences, and on the dimensions (15 m × 40 m) and complexity of the testing environment. These conditions represent an improvement over similar validations performed in simulated scenarios [13] or in smaller areas [19] containing a single gas source [26] and artificially induced unidirectional airflows [30]. The experimental arena is one floor of a university building, in which a hypothetic gas leak can potentially spread very fast and affect many people.…”
Section: Introductionmentioning
confidence: 82%
“…The model was chosen due to its proven performance over small distances. In other words, this model has been used on small scales on many occasions and successfully modeled the dispersion of gas molecules [36][37][38]. The model was effectively applied to NH 3 (g), as the measurements of this pollutant were completed under stable meteorological conditions for a short distance in less than 1 h, which is much shorter than its atmospheric lifetime, τ NH 3 (g) = 1 day [28,39].…”
Section: Gaussian Modeling Of the Point Sourcementioning
confidence: 99%
“…This function is an approximation for a point source of chemical effluent [35]. Other choices, for example, a Gaussian plume model [36], could also be used. Figure 3 (left) shows a surface plot of the fixed time function with these parameters.…”
Section: Chemical Effluent Modelsmentioning
confidence: 99%